Eosinophilic count as a biomarker for prognosis of melanoma patients and its importance in the response to immunotherapy - Moreira, Alvaro; Leisgang, Waltraud; Schuler, Gerold; Heinzerling, Lucie (Immunotherapy, 2017)
AIM: The prognostic role of eosinophils in cancer has been controversial. Some entities such as gastrointestinal cancers show a better survival, while others such as Hodgkin's lymphoma a worse survival in patients with eosinophilia. Patients who exhibited an increase in eosinophils upon therapy with ipilimumab or pembrolizumab were shown to survive longer. We wanted to investigate whether eosinophilia is a prognostic marker in metastatic melanoma. METHODS: In total, 173 patients with metastatic melanoma from our data base (median age 60 years; n = 86 with immunotherapy, n = 87 without immunotherapy) were analyzed for eosinophil counts and survival over the course of 12 years. Eosinophilic count was detected by peripheral blood smear. The ethical committee had approved this retrospective study. RESULTS: Melanoma patients with eosinophilia at any point in their course of disease show a trend toward longer survival independently of their therapy. There is a statistically significant difference for the patients who survive at least 12 months (p < 0.005). In patients with checkpoint inhibitor therapy, survival was significantly prolonged in every patient with eosinophilia (p < 0.05). Furthermore, 69% of the patients treated with immunotherapy experienced at least once an eosinophilia of 5% or greater compared with 46% in the immunotherapy naive-group; for an eosinophilia of 10% values were 30 and 9%, respectively. Interestingly, in patients with more than 20% eosinophils (n = 7) survival was prolonged with a median of 35 months (range 19-60 months) as compared with 16 months (range 1-117 months). CONCLUSION: Eosinophilia is a prognostic marker in patients with metastatic melanoma.
EVALuna2:34325